Comparative study between vector control and direct torque control of induction motor using MATLAB Simulink - Eldali, Fathalla, author; Collins, George J., advisor; Suryanarayanan, Siddharth, committee member; Sakurai, Hiroshi, committee member (Colorado State University. Libraries, 2012)
This thesis project studies and compares two of the most commonly used electric driving methods of induction motors (IM). These methods, which have been used for three decayed are Field Orientation Control (FOC) and Direct Torque Control (DTC). Theoretical background for both methods is explained. Due to its simplicity of use, MATLAB/ SIMULINK is used to simulate the dynamic model of (IM) and applying both techniques on it. The comparative study of speed, torque, and flux is performed under two cases which are the normal operation and in the presence of voltage-sag and short interruption.
Keywords: DTC; induction motor; FOC; electric motor drives